DETERMINATION OF ZIRCON/MELT TRACE ELEMENT PARTITION COEFFICIENTS FROM SIMS ANALYSIS OF MELT INCLUSIONS IN ZIRCON - Thomas J.B.; Bodnar R.J.; Sinha A.K.; Shimizu N. (My University, 2002)
Partition coefficients (zircon/meltDM) for rare earth elements (REE) (La, Ce, Nd, Sm, Dy, Er and Yb) and other trace elements (Ba, Rb, B, Sr, Ti, Y and Nb) between zircon and melt have been calculated from secondary ion mass spectrometric (SIMS) analyses of zircon/melt inclusion pairs. The melt inclusion-mineral (MIM) technique shows that DREE increase in compatibility with increasing atomic number, similar to results of previous studies. However, DREE determined using the MIM technique are, in general, lower than previously reported values. Calculated DREE indicate that light REE with atomic numbers less than Sm are incompatible in zircon and become more incompatible with decreasing atomic number. This behavior is in contrast to most previously published results which indicate D > 1 and define a flat partitioning pattern for elements from La through Sm. The partition coefficients for the heavy REE determined using the MIM technique are lower than previously published results by factors of ≈15 to 20 but follow a similar trend. These differences are thought to reflect the effects of mineral and/or glass contaminants in samples from earlier studies which employed bulk analysis techniques.